2019
DOI: 10.3389/fphys.2018.01881
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Omentin: Their Role in the Crosstalk Between Muscle and Adipose Tissues in Type 2 Diabetes Mellitus Rat Models

Abstract: This study aims to analyze the effects of resisted, aerobic, and combined exercises on omentin levels in visceral adipose tissue and muscle of rats with experimental diabetes to verify whether these adipokines are related to the glucose pathway and inflammation process in this model. Male Wistar rats received a high-fat diet for 4 weeks and a low dose of streptozotocin (35 mg/kg) to induce experimental diabetes. After inducing diabetes, the animals were divided into 4 experimental groups (n = 10): diabetic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 66 publications
(71 reference statements)
2
27
0
Order By: Relevance
“…Increasing exercise intensity also resulted in higher circulating levels of omentin, an adipokine that seems to counteract insulin resistance and obesity (De Souza Batista et al, 2007), improving glucose metabolism through the stimulation of Akt phosphorylation in muscle tissue (Yang, 2006). In line with these results, 12 weeks of aerobic exercise have proven superior to other types of exercise (i.e., resistance exercise and a combination of both resistance and aerobic exercise) for the promotion of omentin production in diabetic animals (de Castro et al, 2019). Similarly, 12 weeks of aerobic exercise have also been reported to result in improved cardiometabolic risk factors (waist circumference, insulin resistance, and lipid profile) together with increased circulating omentin levels in overweight/obese men (Saremi et al, 2010), which has been corroborated in later studies (Wilms et al, 2015; Ouerghi et al, 2017).…”
Section: Discussionmentioning
confidence: 73%
“…Increasing exercise intensity also resulted in higher circulating levels of omentin, an adipokine that seems to counteract insulin resistance and obesity (De Souza Batista et al, 2007), improving glucose metabolism through the stimulation of Akt phosphorylation in muscle tissue (Yang, 2006). In line with these results, 12 weeks of aerobic exercise have proven superior to other types of exercise (i.e., resistance exercise and a combination of both resistance and aerobic exercise) for the promotion of omentin production in diabetic animals (de Castro et al, 2019). Similarly, 12 weeks of aerobic exercise have also been reported to result in improved cardiometabolic risk factors (waist circumference, insulin resistance, and lipid profile) together with increased circulating omentin levels in overweight/obese men (Saremi et al, 2010), which has been corroborated in later studies (Wilms et al, 2015; Ouerghi et al, 2017).…”
Section: Discussionmentioning
confidence: 73%
“…The physiological effects of exercise on adipose tissue could vary depending on the type and amount of exercise. Preceding studies stated that RT (resistance training) and swimming have particularly affected the parameters of body weight, inflammation, and adipocyte areas [32].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that exercise-induced change in omentin might be associated with the beneficial effects of exercise on insulin sensitivity and weight reduction. In addition, De Castro et al [32] have been reported that aerobic training (AT) affects the glucose pathway by stimulating phosphorylation of protein kinase in muscle tissue. In agreement with previous studies, the present research observed a significant rise in the mean serum level of omentin in rats practice swimming as shown in control + swim and HCHF + swim groups compared to control group and HCHF diet group, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…WAT is the main lipid storage site and plays an important role in obesity [6]. In addition to the ability to store energy from the diet [7], WAT-releasing peptide hormones (cytokines) [8], exosomal microRNA (miRNA or miR) [9], and other metabolic agents are involved in the regulation of body energy homeostasis [10]. However, periods of prolonged positive energy balance promote the excessive accumulation of triglycerides and morphological changes that trigger an immune response and pro-inflammatory cytokines secretion, leading to low-grade inflammation [11,12].…”
Section: Introductionmentioning
confidence: 99%